Managing squamous cell carcinoma in recessive dystrophic epidermolysis bullosa with electrochemotherapy - Mafalda Pestana; Margarida Caldeira; Victor Farricha; Sara Carvalhal; Joana Bartolo; Cecília Moura; Joaninha C. Rosa; Emanuel Gouveia; Hugo Nunes; Mariluz Martins (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Epidermolysis bullosa (EB) represents a group of congenital disorders caused by mutations in skin structural proteins. Squamous cell carcinoma (SCC) is one major complication and the leading cause of death of several subtypes of EB. We report a case of a 38-year-old female patient with recessive dystrophic EB that underwent electrochemotherapy (ECT) for treatment of cutaneous SCC in the right foot. Two sessions were performed, in which the intravenous administration of bleomycin was followed by the local application of electric pulses. We verified a partial response in 8th week of follow up and a complete response in the 24th week.   ECT is a local treatment for cutaneous and subcutaneous tumors, mainly as palliative care for metastases. Studies have shown its effectiveness in primary tumors that are unresectable due to size and location, and it has been proposed as a new treatment modality for SCCs in EB with high overall response.